2017
DOI: 10.1111/cyt.12448
|View full text |Cite
|
Sign up to set email alerts
|

An institutional experience with The Paris System: A paradigm shift from ambiguous terminology to more objective criteria for reporting urine cytology

Abstract: The criteria outlined by TPS facilitated the standardisation of urine cytology reporting and significantly increased the sensitivity of diagnosing HGUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…One of the objectives of this study was to examine the rate of atypia between the SJRH system, which was in use during the study period, and TPS which was implemented at our institution in February of 2017 (during the time of case review). A few other recent studies have examined TPS and have reported a reduction in cases reported as atypical . Our results are in agreement with these studies with almost a 50% reduction in AUC compared with AUS.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…One of the objectives of this study was to examine the rate of atypia between the SJRH system, which was in use during the study period, and TPS which was implemented at our institution in February of 2017 (during the time of case review). A few other recent studies have examined TPS and have reported a reduction in cases reported as atypical . Our results are in agreement with these studies with almost a 50% reduction in AUC compared with AUS.…”
Section: Discussionsupporting
confidence: 93%
“…In examining TPS, we are only evaluating cases that were previously diagnosed as AUS and are therefore not assessing the full scope of TPS. This might explain why sensitivity of AUC is decreased as compared with the former AUS category, whereas it is increased in other studies . Although the retrospective pathology review gives a relatively good approximation of diagnosis, it may not always be predictive of how the case would have been signed out.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A major concern of TPS is the potential to miss cases of HGUC. The reported effect on sensitivity for diagnosing HGUC has also varied among studies, with some studies reporting an increase in sensitivity 15 and others reporting a decrease in sensitivity. 16 At our institution, the baseline sensitivity, at >80%, is higher than that of the pre-TPS classification in most other studies, which report 60% to 70% sensitivity for HGUC.…”
Section: Discussionmentioning
confidence: 99%